When and why we disclose distress on SNSs: Perceived affordances, disclosure goals, and anticipated negative evaluations. (December 2021) - Zhao, Pengfei; Lapierre, Matthew A.; Rains, Stephen A.; Segrin, Chris
Abstract: Social networking sites (SNSs) offer unprecedented opportunities for broadcasting self-disclosure. However, questions regarding when and why people tend to post distressing information on SNSs have received insufficient scholarly attention. Rooted in the functional approach of self-disclosure, we investigated how perceived SNS affordances (i.e., network accessibility, visibility, and visibility control) are associated with broadcasting distress disclosure tendencies on SNSs via disclosure goals. Working with 398 college students, we found that people disclose distress on SNSs for seeking support and expressing emotions. However, anticipated negative evaluations can lessen the associations between disclosure goals and distress disclosures on SNSs. Furthermore, the results revealed that network accessibility was indirectly associated with distress disclosures on SNSs via support-seeking goals while visibility control was indirectly related to distress disclosures via emotion expression goals. The indirect effects indicate the importance of studying disclosure goals when investigating the associations between affordances and disclosures. Together, this study advances our understanding regarding online distress disclosures by integrating SNS affordances, disclosures goals, and subjective risks. Highlights: SNS affordances were indirectly associated with distress disclosures on SNSs via disclosure goals. People disclose distress on SNSs for seeking support and expressing emotions. Network accessibility was positively linked to support-seeking goals, which was positively related to distress disclosures. Perceived visibility control was negatively linked to emotion expression, which was linked to more distress disclosures. Anticipated negative evaluations moderated the associations between disclosure goals and distress disclosures on SNSs.